中国民营企业国际化战略的动因和发展--对ZX公司的案例分析=Development of globalization strategy by privately-owned enterprises in China - a case study of ZX company. - Lu, Hong. (2008)
Analysis of the current economic trend of globalization, trying to provide solutions for building sustainable competitiveness of private-owned enterprises, focusing on the globalization strategy of private companies in today's China using the theory of industrial cluster and competitive advantages of International trade.